Stimuli-responsive cylindrical hydrogels mimic intestinal peristalsis to propel a solid object. Issue 15 (14th March 2016) - Nistor, V.; Cannell, J.; Gregory, J.; Yeghiazarian, L.
Abstract : The emerging field of soft robotics relies on soft, stimuli-responsive materials to enable load transport, manipulation, and mobility in complex unconstrained environments. Abstract : The emerging field of soft robotics relies on soft, stimuli-responsive materials to enable load transport, manipulation, and mobility in complex unconstrained environments. These materials often need to replicate biological functionality such as muscle contractions and flexibility. Here we demonstrate a soft actuator prototype based on thermosensitive PNIPAAM hydrogels that can transport and manipulate objects. A hollow cylindrical hydrogel was selectively heated and cooled with Peltier devices to yield a traveling wave of shrinking and swelling akin to intestinal peristalsis. A 4 mm diameter bead was placed inside the cylinder and propelled 19.5 mm, equal to distance traveled by the peristaltic wave. We derived conditions that enable peristaltic transport as a function of transporter-cargo design parameters. We conclude that hydrogel-based peristaltic manipulators covering 2 orders of magnitude in stiffness (1–10 2 kPa) could transport cargo spanning 4 orders of magnitude in size (μm–m).